Bioengineering strategies targeting angiogenesis: Innovative solutions for osteonecrosis of the femoral head - Weihong Zhu; Zhenmu Xu; Ding Zhou; Jiankun Xu; Yuchen He; Zhong Alan Li (Journal of Tissue Engineering)
Osteonecrosis of the femoral head (ONFH) is a prevalent orthopedic disorder characterized primarily by compromised blood supply. This vascular deficit results in cell apoptosis, trabecular bone loss, and structural collapse of the femoral head at late stage, significantly impairing joint function. While MRI is a highly effective tool for diagnosing ONFH in its early stages, challenges remain due to the limited availability and high cost of MRI, as well as the absence of routine MRI screening in asymptomatic patients. . In addition, current therapeutic strategies predominantly only relieve symptoms while disease-modifying ONFH drugs are still under investigation/development. Considering that blood supply of the femoral head plays a key role in the pathology of ONFH, angiogenic therapies have been put forward as promising treatment options. Emerging bioengineering interventions targeting angiogenesis hold promising potential for ONFH treatment. In this review, we introduce the advances in research into the pathology of ONFH and summarize novel bioengineering interventions targeting angiogenesis. This review sheds light upon new directions for future research into ONFH.